Efficacy of two hydrogen peroxide vapour aerial decontamination systems for enhanced disinfection of meticillin-resistant Staphylococcus aureus, Klebsiella pneumoniae and Clostridium difficile in single isolation rooms. Issue 1 (May 2016) - Ali, S.; Muzslay, M.; Bruce, M.; Jeanes, A.; Moore, G.; Wilson, A.P.R.
Summary: Background: Hydrogen peroxide vapour (HPV) disinfection systems are being used to reduce patients' exposure to hospital pathogens in the environment. HPV whole-room aerial disinfection systems may vary in terms of operating concentration and mode of delivery. Aim: To assess the efficacy of two HPV systems (HPS1 and HPS2) for whole-room aerial disinfection of single isolation rooms (SIRs). Methods: Ten SIRs were selected for manual terminal disinfection after patient discharge. Test coupons seeded with biological indicator (BI) organisms [∼10 6 colony-forming units (cfu) of meticillin-resistant Staphylococcus aureus (MRSA) or Klebsiella pneumoniae, or ∼10 5 cfu Clostridium difficile 027 spores] prepared in a soil challenge were placed at five locations per room. For each cycle, 22 high-frequency-touch surfaces in SIRs were sampled with contact plates (∼25 cm 2 ) before and after HPV decontamination, and BIs were assayed for the persistence of pathogens. Findings: Approximately 95% of 214 sites were contaminated with bacteria after manual terminal disinfection, with high numbers present on the SIR floor (238.0–352.5 cfu), bed control panel (24.0–33.5 cfu), and nurse call button (21.5–7.0 cfu). Enhanced disinfection using HPV reduced surface contamination to low levels: HPS1 [0.25 cfu, interquartile range (IQR) 0–1.13] and HPS2 (0.5 cfu, IQR 0–2.0). Both systems demonstrated similar turnaround times (∼2–2.5 h), and no differences were observed in the efficacy of the two systems against BIs ( C. difficile ∼5.1 log10 reduction; MRSA/ K. pneumoniae ∼6.3 log10 reduction). Despite different operating concentrations of hydrogen peroxide, MRSA persisted on 27% of coupons after HPV decontamination. Conclusion: Enhanced disinfection with HPV reduces surface contamination left by manual terminal cleaning, minimizing the risks of cross-contamination. The starting concentration and mode of delivery of hydrogen peroxide may not improve the efficacy of decontamination in practice, and therefore the choice of HPV system may be based upon other considerations such as cost, convenience and logistics.